2006
DOI: 10.1093/hmg/ddi487
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin variants and risk of prostate cancer and tumor aggressiveness

Abstract: We previously reported linkage of a prostate cancer tumor aggressiveness locus to chromosome 7q32-q33, a region also associated with a high frequency of allelic imbalance in prostate tumors. The smallest region of allelic imbalance contains the podocalyxin-like (PODXL) gene, which we evaluate here as a candidate prostate cancer aggressiveness gene mapping to 7q32-q33. DNA from probands of linked families was examined for germ-line mutations in PODXL. A variable in-frame deletion, four missense variants and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 42 publications
3
86
0
2
Order By: Relevance
“…Furthermore, gene expression studies revealed a positive correlation between expression of PODXL and expression of ETS1, a regulator of angiogenesis, in human vascular endothelial cells (11). PODXL has also been implicated in more aggressive forms of prostate cancer (12). The PODXL gene maps to chromosome 7q32-q33 (13), a region that has been linked to aggressive forms of prostate cancer and that exhibits a high frequency of allelic imbalance in prostate tumors (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gene expression studies revealed a positive correlation between expression of PODXL and expression of ETS1, a regulator of angiogenesis, in human vascular endothelial cells (11). PODXL has also been implicated in more aggressive forms of prostate cancer (12). The PODXL gene maps to chromosome 7q32-q33 (13), a region that has been linked to aggressive forms of prostate cancer and that exhibits a high frequency of allelic imbalance in prostate tumors (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Casey et al (45) followed-up reports of linkage and allelic imbalance at 7q32-33 (35,36) by sequencing the gene podocalyxin (PODXL), which is a downstream target of the WT1 tumor suppressor implicated in h-catenin signaling. Somasiri et al had previously reported a correlation between podocalyxin expression and aggressive breast cancer (46).…”
Section: Case-control Studies For Defining Genes Associated With Aggrmentioning
confidence: 99%
“…PODXL has also been found in vascular endothelium, lung, brain, multipotent hematopoietic precursors, megakaryocytes and platelets [4,14,15], as well as in several types of tumors in which the expression levels appear to correlate with the metastatic capacity [16,17,18]. However, unlike the role of PODXL in the renal homeostasis, almost nothing is known about its physiological role in extrarenal tissues.…”
Section: Introductionmentioning
confidence: 99%